Analysing The Application Of Syariah Principles In Malaysia’s Indirect Taxation System - Mohammad Radzi Mohammad Sharif; Selamah Maamor; Abu Sufian Abu Bakar (Mabsya: Jurnal Manajemen Bisnis Syariah, 2024)
The introduction of Malaysia's Goods and Services Tax (GST) spurred a critical examination of its Syariah compatibility. The Malaysian Fatwa Committee endorsed taxation, emphasizing adherence to Syara’ parameters, prompting further exploration, especially concerning indirect taxation systems aligned with Islamic jurisprudence. This paper is focuses on critically analyzing how Syariah principles are currently applied in the formulation and implementation of Malaysia’s indirect tax policies and comprehensively explore the principles of indirect taxation from Syariah perspectives. This study delves into the rich heritage of Islamic economic thought. Renowned scholars such as Abu Yusuf, Al-Qardawi, and Chapra have laid down foundational principles that continue to guide contemporary fiscal policies in Islamic contexts. Employing qualitative methodology, the study conducts content analysis of secondary sources and interviews with key officials from the Malaysian National Fatwa Committee (NFC), Department of Islamic Development Malaysia (JAKIM), Ministry of Finance (MOF) and the Royal Malaysian Customs Department (CUSTOMS). The findings reveal that Islamic scholars have delineated six principles, namely: quality of tax administrations; just, honest, and lenient treatment to taxpayers; fair distribution of income; defining of tax base and rates; flexibility in tax imposition; and approach to tax equity. While the first three principals have been implemented and adhered to, the latter three have been consolidated into the second principle. By bridging historical Islamic perspectives with contemporary policy needs, this study provides guidance for crafting Shariah-compliant especially in indirect tax policies, crucial for good governance and societal well-being. It contributes to Islamic economics discourse and addresses the need for studies evaluating Malaysia's indirect taxation practices' Shariah compliance.